Media dan Sumber Belajar dalam Pembelajaran - Ajri Widiastuti; Asriani; Bagus Sajiwo; Endang Widiana; Muhammad Nur Habibi Barus (Journal of International Multidisciplinary Research, 2024)
Learning media is a container for messages that can clarify the presentation of roles and information, increase teaching intensity, and simplify the learning process. Learning resources can be grouped into message components, people components, tool components, and technical components. Learning resources can also be used as learning media, which can increase and direct student attention, have more direct interaction between students and learning resources, and help students learn individually according to their abilities and interests. Learning media can be grouped into four groups, namely media resulting from print technology, media resulting from audio-visual technology, media resulting from computer-based technology, and media resulting from a combination of print and computer technology. The selection of learning resources and teaching materials must be based on the goals to be achieved, and teaching materials must include exercises that can explore students' thinking abilities. Learning media is part of learning resources and at the same time an integral part of educational technology that needs to be utilized and utilized.